1998
DOI: 10.1016/s1097-2765(00)80055-6
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of p21Cip1/Waf1 and p27Kip1 Mediates Apoptosis in Endothelial Cells through Activation of Cdk2: Role of a Caspase Cascade

Abstract: Apoptosis of human endothelial cells after growth factor deprivation is associated with rapid and dramatic up-regulation of cyclin A-associated cyclin-dependent kinase 2(cdk2) activity. In apoptotic cells, the C termini of the cdk inhibitors p21Cip1/Waf1 and p27Kip1 are truncated by specific cleavage. The enzyme involved in this cleavage is CPP32 and/or a CPP32-like caspase. After cleavage, p21Cip1/Waf1 loses its nuclear localization sequence and exits the nucleus. Cleavage of p21Cip1/Waf1 and p27Kip1 results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
352
9
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(398 citation statements)
references
References 46 publications
34
352
9
3
Order By: Relevance
“…This observation is in total agreement with previous reports showing that the amino terminus of p27 is su cient to bind and to inhibit the cyclin/CDK2 complexes (Luo et al, 1995). In contrast, our data di er from Levkau's study (Levkau et al, 1998) showing that the cleavage of p21 and p27 by a CPP32-like caspase leads to their dissociation from cyclin/CDK2 complexes and to the activation of cyclin A/CDK2. Furthermore, we found that p23 was ®ve to ten times more e cient than p27 in inhibiting CDK2 activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is in total agreement with previous reports showing that the amino terminus of p27 is su cient to bind and to inhibit the cyclin/CDK2 complexes (Luo et al, 1995). In contrast, our data di er from Levkau's study (Levkau et al, 1998) showing that the cleavage of p21 and p27 by a CPP32-like caspase leads to their dissociation from cyclin/CDK2 complexes and to the activation of cyclin A/CDK2. Furthermore, we found that p23 was ®ve to ten times more e cient than p27 in inhibiting CDK2 activity.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is supported by the fact that a putative caspase-3 consensus cleavage sequence exists within p27 sequence (Asp 136 -Ser-Ser-Asp 139 in murine p27 and Asp 136 -Pro-Ser-Asp 139 in human p27). This site can be cleaved in vitro by CCP32 and generates a fragment of 22 ± 23 kDa (Levkau et al, 1998). The analysis of the p27 polypeptidic sequence reveals that this cleavage results in the removal of the nuclear localization signal (Lys 153 to Arg 169 ) and of the CDK2 phosphorylation consensus site Thr 187 -Pro-Lys-Lys 190 at position 187 in the carboxyl terminus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of apoptosis by various stimuli has been shown to require activation of Cdk2 (Levkau et al, 1997;Meikrantz & Schlegel, 1996), while expression of Cdk inhibitors in neurons (Park et al, 1998), or during myocyte di erentiation (Wang and Walsh, 1996), prevented apoptosis. However, in contrast to our studies, cyclin A and not cyclin E-dependent kinases have been implicated in apoptosis of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk1/cyclin B1 activity shields human cells against extrinsic death stimuli (Matthess et al, 2010). Cdk2 activation is mainly detected in apoptotic cells that exhibit G 1 /S phase arrest, as observed in ultraviolet irradiation-treated mesangial cells (Hiromura et al, 2002), etoposide-induced human leukemic cells (Choi et al, 2007;Bastin-Coyette et al, 2011), growth factor-deprived HUVEC cells (Levkau et al, 1998), G-Rh2-induced human hepatoma cells (Jin et al, 2000), panaxadiol-induced SK-HEP-1 cells (Jin et al, 2003). In previous reports, we showed that Cdk2 but not Cdc2 is selectively up-regulated and this upregulation is required for the induction of apoptosis in several cancer cell lines, including SK-HEP-1 cells and HeLa cells induced by treatment with ginsenoside-Rh2 (G-Rh2) (Jin et al, 2000) or panaxadiol (Jin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%